Cellular signaling with nitric oxide and cyclic GMP - Murad,F. (1999)
During the past two decades, nitric oxide signaling has been one of the most rapidly growing areas in biology. This simple free radical gas can regulate an ever growing list of biological processes. In most instances nitric oxide mediates its biological effects by activating guanylyl cyclase and increasing cyclic GMP synthesis. However, the identification of effects of nitric oxide that are independent of cyclic GMP is also growing at a rapid rate. The effects of nitric oxide can mediate important physiological regulatory events in cell regulation, cell-cell communication and signaling. Nitric oxide can function as an intracellular messenger, neurotransmitter and hormone. However, as with any messenger molecule, there can be too much or too little of the substance and pathological events ensue. Methods to regulate either nitric oxide formation, metabolism or function have been used therapeutically for more than a century as with nitroglycerin therapy. Current and future research should permit the development of an expanded therapeutic armamentarium for the physician to manage effectively a number of important disorders. These expectations have undoubtedly fueled the vast research interests in this simple molecule.